A prospective study on possible clinical correlation between peripartum cardiomyopathy and hypertensive disorder in pregnancy - Priyadarshini Pati, Ipsita; Mishra, Arunima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Peripartum cardiomyopathy (PPCM) and hypertensive disorder in pregnancy (HDP) are often seen together. Though their correlation is a matter of research. Methods: A prospective study of 76 patients of HDP in Apollo hospital Bilaspur (C. G.) over a period of one year February 2024 to February 2025 correlation with echocardiography. Results: The maximum number of people with compromised left ventricular ejection fraction (LVEF) function is 28 years. Similarly in our study most of the patients are multigravida which is 22.37%. Maximum patients are of 3rd gravida. Conclusions: Although the majority of HDP women were having normal LVEF function with no signs of PPCM but HDP was associated with markedly increased risks of PPCM that increased with HDP severity. HDP in association with increasing parity and age is also one of the contributing risk factors for PPCM. HDP, severe preeclampsia in particular, probably represents an additional cardiac stress during pregnancy.